Teaching kids is not child’s play - Singapore Management University (Institutional Knowledge at Singapore Management University, 2018)
Staff retention, a brand culture, and governmental commitment is crucial to success in early childhood education Fiona Walker appears to have it all. Happily married with two teenage children, Scottish by parentage but Singapore-born Walker is a leader in her chosen field, as the Group Managing Director of the Singapore-based early childhood education chain Julia Gabriel Education. An industry veteran with 27 years of experience, she also oversees the Chiltern House Preschools and Chengzhu (成竹) Mandarin Centre and Kindergarten and enjoys what she does but admits that very often it involves a fine balancing act.